DIGITAL LITERACY FOR COMMUNITY READINESS IN THE USE OF BLOCKCHAIN TECHNOLOGY FOR ZAKAT PAYMENTS - Bagraff, Halida Achmad; Darmiono, Darmiono (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Islamic financial products with the potential to alleviate poverty include waqf funds, sadaqah, infaq, and zakat. However, a lack of popularity and a number of managerial issues have prevented zakat, infaq, sadaqah, and waqf money from being administered as well as they could have. Zakat management organizations must to adjust to the most recent technology developments in light of these problems. By applying the Technology Readiness Index (TRI) methodology, this study seeks to investigate the preparedness of the Muslim community for the use of blockchain technology for zakat payments. The study population consists of Muslims who have a personal income that reaches the nisab (equivalent to 85 grams of gold within a year) and possess good digital literacy. Purposive sampling was used to choose the 100 respondents who make up the target sample, which was established based on statistical power analysis to guarantee accurate results. Questionnaires were used for data collection, and basic linear regression was used for data analysis. The study's findings show that the community's willingness to use blockchain technology for zakat payments is strongly influenced by digital literacy.